The outdoor urban space vocation for temporariness between past and present - Timothy Daniel Brownlee (Agathón)
The temporariness vocation in the open urban spaces use is an element that strongly characterizes the pre-contemporary city. Even if we have lost evident physical traces, various kinds of temporary devices have always qualified the streets and squares of the cities, being placed side by side with a permanent supporting framework. This paper investigates the potentialities that temporary devices might offer, highlighting the capability that these structures have in adapting to demands of a specific historic period. Finally, it identifies a common thread between present and past, illustrating adaptation scenarios, declining the role of temporariness in those urban areas that most use it.